The Serpent's Trail: William James, Object-Oriented Programming, and Critical Realism - Crockett, Larry J. (Zygon, 2012)
Pragmatism has played only a small role in the half century and more of the science-and-religion dialogue, in part because pragmatism was at a low ebb in the 1950s. Even though Jamesean pragmatism in particular is experiencing a resurgence, owing partly to the work of Rorty and Putnam, it remains inconspicuous in the dialogue. Excepting artificial intelligence and artificial life, computer science also has not played a large role in the dialogue. Recent research into the foundations of object-oriented programming, however, shows this increasingly pervasive practice possesses an implicit pragmatist epistemology. Although science will have to become more computational, it will have to come to terms with both object-oriented computing and its implicit pragmatism, which in turn supports the conclusion that we have fresh warrant for recasting the science-and-religion dialogue in Jamesean pragmatist terms. Some preliminary consequences of such a recasting of the dialogue are explored.